Two-dimensional blind Bayesian deconvolution of medical ultrasound images - Jirík, Radovan; Taxt, Torfinn (IEEE transactions on ultrasonics, ferroelectrics, and frequency control, 2008)
A new approach to 2-D blind deconvolution of ultrasonic images in a Bayesian framework is presented. The radio-frequency image data are modeled as a convolution of the point-spread function and the tissue function, with additive white noise. The deconvolution algorithm is derived from statistical assumptions about the tissue function, the point-spread function, and the noise. It is solved as an iterative optimization problem. In each iteration, additional constraints are applied as a projection operator to further stabilize the process. The proposed method is an extension of the homomorphic deconvolution, which is used here only to compute the initial estimate of the point-spread function. Homomorphic deconvolution is based on the assumption that the point-spread function and the tissue function lie in different bands of the cepstrum domain, which is not completely true. This limiting constraint is relaxed in the subsequent iterative deconvolution. The deconvolution is applied globally to the complete radiofrequency image data. Thus, only the global part of the point-spread function is considered. This approach, together with the need for only a few iterations, makes the deconvolution potentially useful for real-time applications. Tests on phantom and clinical images have shown that the deconvolution gives stable results of clearly higher spatial resolution and better defined tissue structures than in the input images and than the results of the homomorphic deconvolution alone.
Keywords: algoritmy; Bayesova věta; reprodukovatelnost výsledků; Artificial Intelligence; interpretace obrazu počítačem; umělá inteligence; Image Interpretation, Computer-Assisted; Sensitivity and Specificity; senzitivita a specificita; Ultrasonography; ultrasonografie; Reproducibility of Results; Algorithms; Bayes Theorem; Image Enhancement; Pattern Recognition, Automated; rozpoznávání automatizované; vylepšení obrazu